2019
DOI: 10.1111/sms.13521
|View full text |Cite
|
Sign up to set email alerts
|

Cooling during exercise enhances performances, but the cooled body areas matter: A systematic review with meta‐analyses

Abstract: Introduction Hyperthermia during exercise induces central and peripheral fatigue and impairs physical performance. To facilitate heat loss and optimize performance, athletes can hasten body cooling prior (pre‐cooling) or during (per‐cooling) exercise. However, it is unclear whether per‐cooling effect is the same on ‘aerobic’ and ‘anaerobic’ types of exercise (duration <75 and >76 seconds, respectively, according to Gastin [Sports Med 2001;31:725‐741]) and whether the body area that is cooled makes a difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 109 publications
(160 reference statements)
3
44
0
1
Order By: Relevance
“…This is likely because the effectiveness of these types of cooling interventions will be environment dependent, as has been previously illustrated [32]. Of all the external cooling strategies, cold water immersion was the most effective cooling intervention, primarily during precooling but during intermittent cooling as well [66,75,79,89]. Cold water immersion is most effective when cold water is used and the entire body is submerged; this practice, however, is entirely implausible for nearly all occupational settings and likely is only realistic within a sporting context.…”
Section: Personal Cooling Optionsmentioning
confidence: 94%
See 2 more Smart Citations
“…This is likely because the effectiveness of these types of cooling interventions will be environment dependent, as has been previously illustrated [32]. Of all the external cooling strategies, cold water immersion was the most effective cooling intervention, primarily during precooling but during intermittent cooling as well [66,75,79,89]. Cold water immersion is most effective when cold water is used and the entire body is submerged; this practice, however, is entirely implausible for nearly all occupational settings and likely is only realistic within a sporting context.…”
Section: Personal Cooling Optionsmentioning
confidence: 94%
“…The use of cooling packs, cooling collars and wet towels containing ice were other, albeit less effective, cooling options [73,75,89]. This smaller cooling effect, relative to cold water immersion or cooled garments, is likely due to the smaller surface area for cooling of the packs, and the effect appears to be generally uniform regardless of the area of the body applied to (i.e.…”
Section: Personal Cooling Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there is only one meta-analysis (that we recently published) that synthesizes what is known on the impact of cooling different parts of the body on different kinds of physical performance, and the meta-analysis should be considered a companion work of the present narrative review. In the former meta-analysis, we were able to show that per-cooling improves both 'aerobic' and 'anaerobic' exercise performance with a greater benefit for 'aerobic' exercise and that the magnitude of the effect depends on the type and site of the cooling application [28].…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, several studies show that increasing body-cooling during physical exercise (e. g. by using a cooling vest) can prolong its duration [17][18][19][20] and promote thermal comfort [12]. Recent meta-analyses and reviews concluded that cooling vests appeared to be the most effective method in performance improvement [17,18,21,22]. Therefore, it was established that wearing a cooling vest is an efficient cooling technique, especially when it covers a relatively large surface of the body [17].…”
Section: Introductionmentioning
confidence: 99%